Assessing White Shark (Carcharodon carcharias) Behavior Along Coastal Beaches for Conservation-Focused Shark Mitigation - Colefax, Andrew P.; Kelaher, Brendan P.; Pagendam, Daniel E.; Butcher, Paul A. (Frontiers in Marine Science, 2020)
Many large coastal sharks are vulnerable to population declines, however, conflict with human activities often results in unselective culls. Successfully and non-destructively, addressing human-wildlife conflicts requires understanding of animal behaviour. However, knowledge about white shark (Carcharodon carcharias) behaviour near surf zones, where shark bites usually occur, is still limited. We used drones to obtain high-resolution tracks of 108 white sharks directly off coastal beaches on the east coast of Australia. White sharks ranged from 1.9 to 4.0 m (total length) and typically swam parallel to the beach line at an average speed of 0.82 m s-1 (~ 3.0 km h-1), with behaviour being characteristic of energy conserving motion and foraging. Notably the presence of schools of fish increased mean swim speeds of sharks by 0.33 m s-1 and caused tracks to be more convoluted. White sharks were also observed to swim straighter and faster with time either side of midday, increasing predicted mean swim speeds by 0.11 m s-1 and net travel velocities by 0.25 m s-1. White sharks also displayed inquisitive behaviour towards various potential food and non-food items. We demonstrate that white sharks display largely predictable track trajectories and slow movement speeds along coastal beaches, which has utility in further developing non-destructive shark mitigation strategies. Whilst some of the behaviour observed might support the exploratory bite hypothesis, there is likely an increased risk of a shark bite to bathers during situations where there are large shark-attracting food sources present.